Chain DTC Diabetes: new payment system to stimulate integrated care in the Netherlands - de Bruijn, Els M. (Igitur, Utrecht Publishing & Archiving, 2009)
PURPOSE: To examine if the free negotiable chain diagnosis treatment combination (DTC) will stimulate (cost) effective and well organised diabetes care by integrated care groups. CONTEXT: The chain DTC diabetes contains the care in accordance with the medical care standard of the Dutch Diabetes Federation. The care group negotiates the price of the DTC with the insurer. This should stimulate the professionals involved to collaborate as efficient as possible and the insurer to negotiate the lowest price possible. CASE DESCRIPTION: By order of the Ministry of Health, ZonMw (The Netherlands organisation for health research and development) has carried out a program with 10 diabetes care groups, who have experimented the past two years with the chain DTC diabetes and with the organising of integrated care. DATA SOURCES: The program will be evaluated by the RIVM (The National Institute for Public Health and the Environment) on the basis of quantitative and qualitative data. The quantitative data comprise the medical outcome and the organising process of integrated care. The qualitative data comprise open-ended interviews with involved professionals, insurers and patients about their experiences and satisfaction with this way of organising, paying and consuming integrated care. PRELIMINARY CONCLUSIONS: The DTC has indeed facilitated the forming of diabetes care groups. The quality of care seems to be improved, the costs differ between the groups and the place of the patient in the care process differs as well. (Final results expected around November 2009.) DISCUSSION: The chain DTC seems to be a good instrument for improving diabetes care. Applicability for other chronic diseases provokes questions about the total macro costs for chronic care, paying and organising care for multi morbidity and the transition between prevention and care.